STUDI KEMAMPUAN BERBAHASA INGGRIS MAHASISWA NON-ENGLISH DEPARTMENT MELALUI KEGIATAN INTENSIVE COURSE MODEL B (Jurnal Bahasa Lingua Scientia, 2011)
In the overall national development of Indonesia education occupies a strategic position and assumes an important role to play in preparing and equipping its citizens with the necessary knowledge and skills. In this fast changing and developing world, the Indonesian citizens should be able to keep abreast with the rest of the world culturally and scientifically. This implies ability to communicate with people throughout the world through a limited number of internationally accepted and understandable languages, including English. An adequate mastery of English, therefore, is crucial for educated people in Indonesia. One attempt to increase the proficiency of English is the creation of a program called the Intensive English Course (IEC). In order to determine its effectiveness, a study was conducted. This article reviews the background of the study, the methodology, the findings, and the suggestions of the IEC.
Keywords: intensive course; English proficiency